Hazard assessment of benchmark metallic nanomaterials in alveolar epithelial cells - Saruga, Andreia (2018)
Abstract publicado em: Toxicology Letters. 2017;280 (Suppl 1):S180–S190. Disponível em: http://dx.doi.org/10.1016/j.toxlet.2017.07.523